Esensi Perayaan Siwaratri: Konsep dan Implementasinya dalam Konstruksi Pengetahuan Keagamaan Menuju Pencerahan - I Made Pasek Subawa (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
Siwaratri celebration can be said to be a socio-religious construction, this is in view of the externalization element in the form of a Siwaratri concept, objectivation (institutionalization of ritual processes and self-discipline to worship God in its manifestation as a memalina), and internalization, namely the absorption of values ​​and norms in Siwaratri Celebration. as a foundation in realizing the consolidation of hopes, beliefs, awakening mental attitude towards enlightenment and liberation.The construction process is carried out by rearranging information about Siwaratri in the form of knowledge, beliefs, beliefs, values ​​and attitudes, traditions, and patterns of certain actions obtained in this religious practice into a powerful information structure, in a meaningful sense , based on values, integrated and always actively looking to always be reflected back. Knowledge and beliefs about Siwaratri are not objective realities that exist outside of humans, but active reconstruction in the human mind when interacting in religious life and at the same time these beliefs can rebuild certain knowledge, values, and actions that are useful for the subject (Hindus) especially in building personal, structural, and social piety.